Exigências ambientais europeias: novos desafios competitivos para o complexo eletrônico brasileiro - Ansanelli, Stela Luiza de Mattos [UNESP] (My University, 2011)
The objective of this paper is to evaluate the implications of the european environmental requirements for electronic equipment on brazilian electronic industry sector. These deter-minations deal with elimination of hazardous substances and management of electronic products waste and have reached not only the electronic sector companies in international level, but brazilian electronic sector as well. Most brazilian companies of the electronic sector are getting complied with the requirement that restricts the use of hazardous substances. The main consequences of this process are technological innovations and changes on contractual relationships among companies. Foreign companies branches are more advanced than local ones in terms of timing of compliance to the new requirements and technological perfor-mance, showing an alignment with headquarter strategies. Not being complied with these requirements avoid companies to achieve commercial benefits and open space for questions about policies Brazil must take.

O objetivo deste artigo é avaliar as implicações das exigências ambientais europeias para equi-pamentos eletroeletrônicos sobre o complexo eletrônico brasileiro. Essas determinações, que tratam da eliminação de substâncias perigosas e da gestão dos resíduos de produtos eletrônicos, têm atingido não só as empresas do setor em nível internacional, mas também o complexo eletrônico brasileiro. A maior parte das empresas do setor no Brasil está se adequando ao requisito que restringe o uso de substâncias perigosas. Os principais efeitos desse processo são o desenvolvimento de inovações tecnológicas e alterações nas relações contratuais entre as empresas do setor. As filiais estrangeiras estão mais avançadas do que as nacionais quanto ao período de ajuste às novas regras e ao desempenho tecnológico alcançado, sinalizando um alinhamento com as estratégias das matrizes. O descumprimento dessas exigências pelas empresas nacionais evita ganhos comerciais e gera indagações quanto às políticas que devem ser adotadas pelo país.
European environmental requirements: new competitive challenges for brazilian electronical sector
Keywords: Electronic Sector; European Environmental Requirements; Setor Eletrônico; Normas Ambientais Européias